Partnership of science and business in socially innovative project management - Miszczak, Katarzyna (Partnerstwo nauki i biznesu w zarządzaniu projektem innowacyjnym społecznie, 2015)
Due to the modern developmental challenges, more and more often in the discussion of the transfer of knowledge, new technologies and modernization of the intelligent economy there appear social innovations. An effective way of promoting the implementation of social innovations seems to be indirect actions, involving the creation of a good climate for innovativeness, entrepreneurship and creativity. The examples of such activities dedicated to improving the quality of local space are intensively developed networks of cooperation between the sectors of science and economic activity. The aim of the study is characterization of the role of science and business partnerships in the effective management of projects, in particular socially innovative projects. The paper offers mainly descriptive method on the example of an application project entitled “NEMO Creativity Station – Social Innovation for Communes.” The object of the research is a socially innovative service offered to users of the local public space in Polish communes, promoting mentally and physically healthy lifestyle
Biblioteka Regionalisty, 2015, Nr 15, s. 73-82
Keywords: partnership of science and business; social innovation; project management; partnerstwo nauki i biznesu; innowacja społeczna; zarządzanie projektem